MODIFIKASI GERGAJI TANGAN ELEKTRIK UNTUK MEMOTONG MATA TUNAS TEBU (Saccharum offichinarum L) - Siswoyo Soekarno; Sakli Petiet Isbi Kurniawan; Setyo Harri (Faculty of Agricultural Technology, University of Jember, 2014)
Generally the multiplication of sugarcane was conducted by cutting. The latest methods in sugarcane plant propogation using methods budchip. Criteria that must be met from the seed cane chunk with budchip methods, namely: (1) the buds are not injured, (2) has a root cuttings. This study aims to make design and performance testing of sugarcane buds mower. Stages of research: (1) identification of problem, (2) design, (3) assembly , and (4) testing machine includes functional testing and testing elemtary. The results showed that buds cane cutting machine has a capacity 1900 shoots/hour and Yield efficiency of 92.3%. Break-event point (BEF) has been achieved when producing 321.071,4 buds during 33 days.Keywords: bud chip, cutting capacity, cutting results, effisiensi, and analysis economy